Modified RSA Cryptosystem with Data Hiding Technique in the Terms of DNA Sequences - Sahay, Harsh (International Journal of Computer Sciences and Engineering, 2019)
RSA algorithm is an efficient algorithm for preventing unauthorized access over the network. But there are some drawbacks of RSA algorithm such as its high computational time. In this work we are reducing the computational time of RSA algorithm and increasing security of RSA algorithm. In this work we are modifying security of RSA algorithm by using three prime numbers instead of two as used in RSA algorithm. For reducing computational time of RSA algorithm to each character, multiple characters are merged together to form a merged unit. For merging each character cantor’s pairing algorithm has been used. The merged unit is now encrypted to the network. To the receiver side cipher text is received. After decryption, the merged data unit is received to the receiver side. After going to cantor’s unpairing algorithm individual characters of merged data unit are displayed to the receiver side .The highlight of this work is it increases efficacy of RSA cryptosystem. This modified work reduces computational time of RSA algorithm, even increases security of this algorithm. Even In this work we are hiding cipher text in the terms of DNA sequences. So that it is very difficult for intruders to get a real DNAsequence.